Want But Do Not Need : The Kalipare Village Community's Response to the COVID-19 Vaccine Program in Malang Regency - Anton Sujarwo,; Atik Triratnawati, (Indonesian Journal of Medical Anthropology, 2022)
The pandemic caused by COVID-19 is still ongoing after nearly two years. The hope that the pandemic will be over soon is beginning to emerge. The successful development of a COVID-19 vaccine is one of the efforts to combat the pandemic. Vaccination programs that are available to the general public do not always run smoothly. The vaccination program was overshadowed by a number of issues and polemics. The purpose of this research is to see how the community reacts to the COVID-19 vaccination program. Data was collected using ethnographic research methods in Kalipare Village, Malang Regency, between October and November 2021. Random informants and interviews were conducted on members of the community and health professionals. The analysis was carried out by categorizing the data related to the community's fear, willingness, or doubt in participating in this program. According to the findings of this research, public rejection, fear, and doubt occur as a result of: a lack of public confidence in the vaccine's effects; a lack of trust in institutions; and the assumption that vaccines can cause illness and death. Typically, research on vaccine scepticism is followed by a refusal to participate in the program, but the findings of this research show the opposite. People continue to participate in the vaccination program despite their lack of faith, doubt, and fear.